Supergods what masked vigilantes, miraculous mutants, and a sun god from Smallville can teach us about being human - Morrison, Grant (New York Spiegel & Grau, 2011)
Morrison draws on history, art, mythology, and his own astonishing journeys through this alternate universe as a comic book writer to provide the first true chronicle of the superhero.
The sun god and The dark knight -- Lightning's childl -- The superwarrior and the Amazon princess -- The explosion and the extinction -- Superman on the couch -- Chemicals and lightening -- The fab four and the birth of the marvelous -- Superpop -- Infinite earths -- Shamans of Madison Avenue -- Brightest day, blackest night -- Feared and misunderstood -- Fearful symmetry -- Zenith -- The hateful dead -- Image versus substance -- King Mob : my life as a superhero -- Man of muscle mystery -- What's so funny about truth, justice, and the American way? -- Respecting authority -- Hollywood sniffs blood -- Nu marvel 9/11 -- The day evil won -- Iron men and incredibles -- Over the event horizon -- Star, legend, superhero, supergod? -- Outro: 'nuff said.
Includes bibliographical references and index.
UCWS-3123g donated by Carljoe Javier - September 2017
Keywords: Comic books, strips, etc. -- United States; Superheroes -- United States